2016
DOI: 10.1513/annalsats.201509-603oc
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Interventions to Teach Metered-Dose and Diskus Inhaler Techniques. A Randomized Trial

Abstract: Rationale: The most effective approach to teaching respiratory inhaler technique is unknown.Objectives: To evaluate the relative effects of two different educational strategies (teach-to-goal instruction vs. brief verbal instruction) in adults hospitalized with asthma or chronic obstructive pulmonary disease. Methods:We conducted a randomized clinical trial at two urban academic hospitals. Participants received teach-to-goal or brief instruction in the hospital and were followed for 90 days after discharge. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 20 publications
(33 reference statements)
4
78
0
1
Order By: Relevance
“…Poor performance with MDIs has been found in multiple other studies, with error rates similar to those found in our study. [20, 31] In our analysis of individual steps, the most errors for both MDIs and Advair were errors of breathing—breath holding, appropriate rate of inhalation, full exhalation, etc. Careful coordination of breathing and breath holding may be difficult for subjects with cough or dyspnea, and is a much more subjective maneuver for a patient to perform in comparison to steps such as twisting the device or pressing to actuate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor performance with MDIs has been found in multiple other studies, with error rates similar to those found in our study. [20, 31] In our analysis of individual steps, the most errors for both MDIs and Advair were errors of breathing—breath holding, appropriate rate of inhalation, full exhalation, etc. Careful coordination of breathing and breath holding may be difficult for subjects with cough or dyspnea, and is a much more subjective maneuver for a patient to perform in comparison to steps such as twisting the device or pressing to actuate.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study examining methods of inhaler instruction for hospitalized patients with asthma and COPD found that subjects with low health literacy responded well to the intervention. [31] This suggests that while low educational attainment and health literacy may predict worse technique, they are not a barrier to improvement. Lack of knowledge about inhalers on the part of providers is a significant issue [32] that must be separately addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,21–22 However, we have also shown that the improved inhaler technique initially obtained through TTG wanes within 30 days post-discharge. 22 Since providing in-person inhaler teaching post-discharge is often impractical, but reinforced teaching is necessary, a need exists for an effective, portable education strategy that remains accessible to patients both in-hospital and post-discharge.…”
Section: Introductionmentioning
confidence: 74%
“…In addition, the CHICAGO Plan ED Coordinator, a member of the study team, provides all participants two metered dose inhaler (MDI) spacers free-of-charge and uses teach-to-goal methodology (repeated rounds of education and evaluation until the child achieves mastery) to educate the child and the caregiver about appropriate inhaler technique for a MDI. (13,14) Patient education regarding the MDI device was selected because it is commonly used for quick-relief medications and is also the device for many inhaled controller medications. Stakeholders identified the need for all participants to benefit as a central aspect of the study design to ensure adequate support of the CHICAGO Plan by clinical staff and caregivers.…”
Section: Design and Methodsmentioning
confidence: 99%